Coproduto de soja (Okara) na alimentação de vacas da raça holandesa em lactação - Durman, Thomer (2015)
Aiming to improve the economic efficiency and performance of the dairy production system, several studies have used agro-industrial by-products as ingredients in livestock rations. Thus, an experiment was conducted utilizing four lactating Holstein dairy cows fed increasing levels of okara inclusion in the concentrate (0, 10, 20 and 30%) and distributed in a latin square design. It was evaluated the intake of: dry matter; crude protein; lipids and neutral detergent fiber, the apparent nutrients digestibility and in vitro digestibility of the treatments also were evaluated. There was decreasing linear effect (P=0.0162) for dry matter in vitro digestibility, being indirectly proportional to the inclusion of okara. It was also observed quadratic effect (P=0.0345) for neutral detergent fiber intake, being directly proportional to the by-product inclusion, with maximum value at 9.31 kg of neutral detergent fiber intake in the 20% inclusion of okara treatment. Others parameters did not differ significantly regarding the treatments. In addition, the performance and milk quality was evaluated, as well as economic feasibility of okara inclusion in the diet. There was no significant difference for milk production, fat, protein, lactose, milk urea nitrogen and somatic cells count. Regarding the economic analysis, it was reported that the best results for average feed cost, gross margin, breakeven and profitability index. Therefore, it was concluded that including up to 30% of soybean by-product (okara) in lactating cows concentrate shows promising results of its use, featuring to the product a great potential for use.